2012
DOI: 10.1016/j.bmcl.2011.12.111
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the estrogen receptor with metal-carbonyl derivatives of estradiol

Abstract: As part of our program to develop new probes for the estrogen receptor binding domain, we prepared and evaluated a novel 17α-(rhenium tricarbonyl bipyridyl) vinyl estradiol complex. Preparation of the final compound was achieved using the Stille coupling between the preformed brominated rhenium tricarbonyl bipyridine complex and the tributylstannyl vinyl estradiol. Competitive receptor binding assays and stimulatory assays demonstrated that the final complex retained affinity and efficacy comparable to the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Estrogenic steroid conjugates possessing metal chelates at the 17α-position represent an attractive delivery vector as a targeting strategy [ 89 , 90 , 91 , 92 ]. In this regard, Zhang et al synthesized a new series of estrogen-derived metal complexes and applied the squaramide structure as the core of the metal binding unit.…”
Section: Metal Complexesmentioning
confidence: 99%
“…Estrogenic steroid conjugates possessing metal chelates at the 17α-position represent an attractive delivery vector as a targeting strategy [ 89 , 90 , 91 , 92 ]. In this regard, Zhang et al synthesized a new series of estrogen-derived metal complexes and applied the squaramide structure as the core of the metal binding unit.…”
Section: Metal Complexesmentioning
confidence: 99%
“…40 Recently, Hanson et al reported the synthesis of the 17αsubstituted estradiol 180 via a Stille coupling reaction 61 between the rhenium complex 179 and the stannylvinyl estradiol 178, the latter being derived from a hydrostannation of ethynyl estradiol 75 (Scheme 50). 100 The coupling reaction between 178 and 5-bromo-2,2′bipyridine remained unsuccessful, and the prechelated Re compound 179 was found to be a good alternative owing to the beneficial electron-withdrawing effect of the metal in such a reaction.…”
Section: Tridentate Sxs-type Chelates (X = N O S)mentioning
confidence: 99%
“…Recently, Hanson et al reported the synthesis of the 17α-substituted estradiol 180 via a Stille coupling reaction between the rhenium complex 179 and the stannylvinyl estradiol 178 , the latter being derived from a hydrostannation of ethynyl estradiol 75 (Scheme ) …”
Section: Potential Radiopharmaceuticalsmentioning
confidence: 99%
“…That effect should occur at levels below those at which toxicity is generated in normal cells, or non ER-selective cells. The targeting component should not interfere with the therapeutic responses. ,,, The process by which ER-targeted conjugates should be screened was described in excellent detail by Katzenellenbogen et al These methods include an initial screening through a series of assays to demonstrate its effectiveness as a ligand with high binding affinity for ER, potent efficacy in an appropriate assay, selective activity in ER-dependent but not ER-negative breast cancer cells, that is reversible by exposure to estradiol.…”
Section: Evolution Of Antiestrogen–drug Conjugatesmentioning
confidence: 99%